ASSESSMENT OF 16-YEAR-OLD FEMALE BASKETBALL PLAYERS WITH CHRONOJUMP SYSTEM - Mariana Borukova; Ivan Kalinov (Scientific Publishing House. NSA Press, 2024)
In the basketball game, lower extremity strength plays a key role in various game actions. The jumping mat (Chronojump), an open-source (free software and open hardware), is available to the public on official servers, emphasizing peer review and corrections by the user community. The aim of this study was to establish the explosive power of the lower limbs of 16-year-old female basketball players from the Bulgarian National Basketball Team. We used specialized software, a signal transducer, and an electro-contact mat Chronojump. The subject of the study was the explosive power of the lower limbs of 16-year-old female basketball players from the national team of Bulgaria. The object of the study was the performance of the Chronojump platform tests to establish the explosive strength of the lower limbs. The study was conducted among 16 active female basketball players selected for the Bulgarian national team. Each participant performed all jumps at the same time of day. They performed CMJ - 90-degree squat jump; SJ - Squat, two-second hold, and jump; CMJAT - Jump with arms extended forward and up; RCMJ - Manipulative 90-degree squat jump; Stiff ness - Manipulative ankle jump. The test's mathematical-statistical results were processed with variance analysis and One-way ANOVA, with a critical value of the F-criterion (F = 2.38) and high statistical reliability (Pt ≥ 95%). Results showed that hand involvement is key in rebounding. In terms of jumping endurance and explosiveness quotient, female athletes had a lower level of development. This research has the potential to significantly impact the training and performance of female basketball players.